Sexual behaviour and practices among adolescents and young people: study and results from a tertiary care centre of north India - Agarwal, Neni; Brar, Balvinder Kaur; Kumar, Sumir; Rajoa, Onkar Singh; Chahal, Anahita (International Journal Of Community Medicine And Public Health, 2021)
Background: Adolescence and young age is a time of opportunity and risk. During this time, attitudes, values and behaviours that forms a young person’s future begin to develop and take shape. The World Health Organization (WHO) estimates that 70% of health related issues in adults are largely due to behaviours initiated during adolescence. Age of sexual debut is generally low, yet there is dearth of knowledge on sexuality. Methods: This prospective study was conducted on adolescents and young people visiting the dermatology out patient department of a tertiary care centre in north India over 6 months duration with the help of a self administered questionnaire regarding sexual health and practices followed by imparting knowledge regarding safe sexual practices by the author. Results: Sexual debut is usually with an elder as noted in the study. Youngsters engage in unhealthy sexual behaviours, characterized by early age at sexual initiation, unsafe sex and multiple sex partners, Reasons given for this include curiosity, peer influence, pleasure and financial benefit, amongst others. Conclusions: Similar patterns of sexual behavior have been seen in all parts of the world, the findings being similar in developed as well as developing nations. Despite the ongoing programs and initiatives taken by the Indian government, this article points to the need of increasing sexual awareness by incorporating sexual education as a part of the early education curriculum, by helping and including parents to overcome the social and cultural barrier between them and their children. Encouraging contraceptive use and hence improving adolescent and young people’s reproductive and sexual health in the country.